2022
DOI: 10.3390/f13111782
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Comprehensive Effect of Different Agroforestry Intercropping Modes on Poplar

Abstract: Forest–agriculture complex management is an efficient planting mode that can effectively improve soil utilization and bring greater economic value. However, this planting model has not yet been systematically carried out in the northeast of China. Thus, to provide a theoretical basis for agriculture and forestry intercropping in northeast China, the variation in the growth and wood characteristics of Populus cathayana × canadansis ‘xin lin 1’ and the economic benefits of intercropping crops under different int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Poplar is one of the fastest growing timber species and has the largest planted area in the world’s mid-latitude plains ( Hou et al, 2019 ). In 2016, the IPC (International Commission on Poplar and Other Fast-growing Trees that Sustain People and the Environment) reported that the total area of poplar cultivation worldwide had increased to 31.4 million hm 2 ( Lu et al, 2022 ). A large number of poplar forests are planted in the state-owned mechanical forest farm in Xinmin City, Liaoning Province, China.…”
Section: Introductionmentioning
confidence: 99%
“…Poplar is one of the fastest growing timber species and has the largest planted area in the world’s mid-latitude plains ( Hou et al, 2019 ). In 2016, the IPC (International Commission on Poplar and Other Fast-growing Trees that Sustain People and the Environment) reported that the total area of poplar cultivation worldwide had increased to 31.4 million hm 2 ( Lu et al, 2022 ). A large number of poplar forests are planted in the state-owned mechanical forest farm in Xinmin City, Liaoning Province, China.…”
Section: Introductionmentioning
confidence: 99%